REVIEW OF MALPRACTICE AMONG LAND DEED OFFICIALS FROM THE POINT OF CRIMINAL LAW - Putri, Destia Liana; Gunadi, Ariawan (Faculty of Law-Universitas Bandar Lampung, 2021)
This study discusses malpractice among PPAT related to alleged violations of the law against the deed he made. This was motivated by the presence of PPAT who was suspected of committing an act that was indicated as a crime so that it was reported to the Police Investigator. In this case, it is necessary to prove the truth because the PPAT deed is an authentic deed that is binding on the parties and is perfect, then PPAT has its own Code of Ethics and Law that must be obeyed. The purpose of this study was to determine the criteria for malpractice PPAT? Criminal liability if PPAT commits malpractice? The ideal supervision reconstruction of PPAT in terms of minimizing the occurrence of malpractice among PPAT? The research method used in this research is using normative juridical research methods, namely library law research supported by interviews. The results showed that the criteria for malpractice PPAT must meet 7 legal signs which are instructions that must be obeyed by PPAT, in cases that have occurred if PPAT actually commits malpractice, criminal sanctions are applied in Article 263 of the Criminal Code regarding letter falsification, the supervisory mechanism for PPAT is divided in 3 levels, namely Regional, Regional and Central